Fremtidige opgaver i den landbrugsfaglige uddannelse i Danmark. - Rasmussen, A. O.; Hartvig Larsen, P. (Tidsskrift for Landøkonomi, 2018)
Fremtidige opgaver i den landbrugsfaglige uddannelse i Danmark.